Effect of applied cathodic current on Al brass coolers to control sulphate scales in sea water - Rincón, Alvaro; de Rincón, Oladis; Loaiza, Edgar (Rev. Téc. Fac. Ing. Univ. Zulia, 2011)
The objetive of the present reseach paper was to study the effect of applied current to polar1ze cathodically the inner surface of tubes, to control sulphate depositions in Heat Exchangers using sea water as a cooling fluid. A Ti/ Pt anode was used to polarize the internal surface of the Al-brass ASTM B-111 type B lubes (3/ 4 in diameter). Several experimental tests were run to study the efficiency of the system. In these, the current applied was varied while keeping both the flow (Q) and the outlet temperature (Ts) of the sea water steady. The scale samples formed in the pipes during each of the tests were identified by X-Ray fluorescence, chemical analysis of cations and anions and turbidimetric analysis. The results show that up to 80 % of sulphate ions lo the scale can be inhibited. It was also found that the amount of scale deposited on the, surface where the anode was located is a function of the applied current: the lower the current the greater the inhibited. However, the applied current produced no variation on the scale deposition in the area away from the anode location.